2011
DOI: 10.1111/j.1365-2761.2011.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence properties of Moritella viscosa extracellular products

Abstract: Moritella viscosa is the causative agent of winter ulcer disease of marine fish. Knowledge of its pathogenicity is limited and there are no reports comparing the virulence properties of a collection of bacterial isolates. The in vivo and in vitro virulence of the extracellular products (ECP) of 22 M. viscosa isolates was screened. Two non-virulent Canadian isolates and a Norwegian isolate with reduced virulence produced non-lethal ECP. Correlation was obtained between cytotoxin and haemolysin production of M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The isolates include both typical and variant M. viscosa , which were categorized as per standard biochemical and phenotypic methods as well as sequence analysis [2, 5, 8, 21]. The complete genome of the virulent M. viscosa MV 0609139 [22, 23] was used as reference.…”
Section: Methodsmentioning
confidence: 99%
“…The isolates include both typical and variant M. viscosa , which were categorized as per standard biochemical and phenotypic methods as well as sequence analysis [2, 5, 8, 21]. The complete genome of the virulent M. viscosa MV 0609139 [22, 23] was used as reference.…”
Section: Methodsmentioning
confidence: 99%
“…Ulcerative lesions are likely to be initiated by a series of factors that lead ultimately to a breach of the normal barrier function of the skin (reviewed in [264]). In this sense, the bacteria Moritella viscosa is considered the agent causing winter ulcer diseases characterized by extensive and chronic ulceration of the skin and septicaemia [269][270][271][272]. Recently it has been demonstrated that this bacteria (but not A. wodanis) affected or inhibited the epidermal regeneration abilities of keratocytes [273].…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%
“…). Little is known of M. viscosa virulence, but its extracellular products (ECPs) are both cytotoxic to fish cells and lethal to Atlantic salmon (Bjornsdottir, Gudmundsdottir & Gudmundsdottir ). It is further anticipated that environmental factors such as temperature and the status of skin health are important factors for susceptibility to infections (Tunsjø et al .…”
Section: Introductionmentioning
confidence: 99%